1962
DOI: 10.1099/00221287-27-1-51
|View full text |Cite
|
Sign up to set email alerts
|

A Defined Medium for Haemophilus influenzae and Haemophilus parainfluenzae

Abstract: SUlMMARYA defined medium is described for the growth of H-hilus i r J~a e and I?. puraifi$mae which can be used either as a liquid medium or solidified with agar.The purine and pyrimidine, vitamin, amino acid and mineral salt requirements for three strains have been analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
5

Year Published

1962
1962
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 4 publications
0
17
0
5
Order By: Relevance
“…One apparently significant variation was the size of the inoculum, which ranged from single cells on agar media to as high as 107 cells for cultures in fluid media (Gilder and Granick, 1948 ;Brumfitt, 1959 ;Butler, 1962;Parker and Hoeprich, 1962).…”
Section: H a E M I N A N D N I C O T I N A M I D E A D E N I N E D I mentioning
confidence: 99%
“…One apparently significant variation was the size of the inoculum, which ranged from single cells on agar media to as high as 107 cells for cultures in fluid media (Gilder and Granick, 1948 ;Brumfitt, 1959 ;Butler, 1962;Parker and Hoeprich, 1962).…”
Section: H a E M I N A N D N I C O T I N A M I D E A D E N I N E D I mentioning
confidence: 99%
“…was first observed by Avery in 1918; Butler (1962) found that this substance could replace serum albumen in a semidefined medium for Haemophilus and suggested that its role may be that of a protective colloid. Albumen, starch and charcoal have a similar effect in media for the growth of other pathogens (Dubos and Davis, 1946;Casman, 1947;Mazloum and Rowley, 1955).…”
Section: Discussionmentioning
confidence: 99%
“…Smears of growth of the same age taken from CTA slopes show predominantly well-defined rods for strain R d l and FID, while strain Rd is predominantly cocco-bacillary. On a medium containing Zeo-carb treated yeast extract (Butler, 1962) strain Rd would not grow, but strains R d l and FID gave reduced growth which was stimulated in both organisms by the addition of amino acids. The vitamin and amino acid requirements were exactly those of strain FID, both requiring pyridoxine, isoleucine, and valine as essential L. 0.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarizes the results obtained concerning the purine, pyrimidine, amino acid and mineral salt requirements of strain Rdl, obtained during the development of SM previously reported. The growth requirements of strains Rd, RdTr, and FID were ascertained at the same time and have been reported elsewhere (Butler, 1962). It will be noted that strain R d l has an essential requirement for uracil, pyridoxine, isoleucine and valine.…”
Section: Resltltsmentioning
confidence: 99%
See 1 more Smart Citation